Efecto de la adición de citrato de sodio sobre las propiedades reológicas y nutricionales del surimi de calamar gigante (Dosidicus gigas) - Escobedo, F. (2023)
The rheological and nutritional properties of giant squid (Dosidicus gigas) surimi prepared by acid-saline leaching and the generation of a sol colloid with sodium citrate were evaluated. The application of 0.25, 1.27, 2.0, 3.0 and 7.0% sodium citrate produced a sol colloid from giant squid myofibrillar proteins. The addition up to 3.0% of sodium citrate presents a positive linear correlation with the properties of hardness and strength, from 2.0% there is a directly proportional increase with the modulus of elasticity of the gel. The addition of citrate as a cryoprotectant in the product did not improve the protective effect during storage at -20 °C for 72 hours. The replacement of NaCl by sodium citrate improved the texture of the surimi, a change that in terms of healthy eating contributes to the cleanliness of the nutritional label of the product by reducing its sodium content to 57.8% and not exceeding the limit of 800 mg/100 g of solid food.